Mapping of sequences required for mouse neurovirulence of poliovirus type 2 Lansing. - La Monica, N (1986)
Intracerebral inoculation of mice with poliovirus type 2 Lansing induces a fatal paralysis, while most other poliovirus strains are unable to cause disease in the mouse. To determine the molecular basis for Lansing virus neurovirulence, we determined the complete nucleotide sequence of the Lansing viral genome from cloned cDNA. The deduced amino acid sequence was compared with that of two mouse-avirulent strains. There are 83 amino acid differences between the Lansing and Sabin type 2 strain and 179 differences between the Lansing and Mahoney type 1 strain scattered throughout the genome. To further localize Lansing sequences important for mouse neurovirulence, four intertypic recombinants were isolated by exchanging DNA restriction fragments between the Lansing 2 and Mahoney 1 infectious poliovirus cDNA clones. Plasmids were transfected into HeLa cells, and infectious recombinant viruses were recovered. All four recombinant viruses, which contained the Lansing capsid region and different amounts of the Mahoney genome, were neurovirulent for 18- to 21-day-old Swiss-Webster mice by the intracerebral route. The genome of neurovirulent recombinant PRV5.1 contained only nucleotides 631 to 3413 from Lansing, encoding primarily the viral capsid proteins. Therefore, the ability of Lansing virus to cause paralysis in mice is due to the viral capsid. The Lansing capsid sequence differs from that of the mouse avirulent Sabin 2 strain at 32 of 879 amino acid positions: 1 in VP4, 5 in VP2, 4 in VP3, and 22 in VP1.